2019
DOI: 10.3325/cmj.2019.60.166
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 level, cognitive performance, and severity of depressive symptoms in patients treated with systemic anticancer therapy: a prospective study

Abstract: Aim To assess the relationship between cognitive functions, severity of depressive symptoms, and expression of interleukin 1 (IL)-1 in patients treated with systemic anticancer therapy. Methods This prospective study, conducted in 2017-2018, involved 55 patients (56% men) subjected to systemic anticancer therapy. Forty-one patients had lung cancer (74.55%) and 14 had breast cancer (25.45%). Patients’ mean age was 55.5 ± 9.3 (from 26 to 65 years). Neuropsychological test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Interestingly, a study conducted in 2017-2018 explored the relationship between cognitive function, severity of depressive symptoms, and IL-1 expression in patients with BC treated with systemic anticancer therapy. The protein expression levels of IL-1α and IL-1β in patients after chemotherapy were significantly lower, and the severity of depressive symptoms was also lower than that before chemotherapy [151]. We need a more detailed understanding of how different types of cells interact in the microenvironment and how IL-1 signaling promotes or suppresses tumors to better use immune cells and IL-1 as targets and biomarkers for BC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study conducted in 2017-2018 explored the relationship between cognitive function, severity of depressive symptoms, and IL-1 expression in patients with BC treated with systemic anticancer therapy. The protein expression levels of IL-1α and IL-1β in patients after chemotherapy were significantly lower, and the severity of depressive symptoms was also lower than that before chemotherapy [151]. We need a more detailed understanding of how different types of cells interact in the microenvironment and how IL-1 signaling promotes or suppresses tumors to better use immune cells and IL-1 as targets and biomarkers for BC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Five of 6 studies (83%) found an association between depression and inflammation while patients were receiving chemotherapy. [37][38][39][40][41][42] All 4 studies of patients receiving radiation therapy revealed an association between depressive symptoms and inflammation. [43][44][45][46]…”
Section: Quality Assessmentmentioning
confidence: 99%
“…A cumulative meta-analysis on relationships between pro-inflammatory cytokines and depression failed to clarify the correlation between depression and IL-1β because the existing results were very inconsistent (Haapakoski et al, 2015). However, Jasionowska et al (2019) also found a negative (but not significant) correlation between depressive symptoms and IL-1β in patients with cancer prior to systemic anticancer treatment. Furthermore, we did not find significant differences of IL-6 and TNF-α among the three groups and did not find any significant associations of depressive symptoms with them in patients with BC.…”
Section: Discussionmentioning
confidence: 79%